Enabling Catalytic Oxidation of Li2O2 at the Liquid–Solid Interface: The Evolution of an Aprotic Li–O2 Battery. Issue 4 (29th January 2015) - Feng, Ningning; He, Ping; Zhou, Haoshen
Abstract We show that by using a suitable soluble redox mediator, the charging overpotential can be reduced and the round‐trip efficiency can be improved in an aprotic Li–O2 battery. Not only do we explore a new redox couple, 10‐methyl‐10H‐phenothiazine, as a soluble catalyst that improves the electrochemical performance, but we also propose possible challenges that need to be overcome for the future improvement of aprotic Li–O2 batteries.